Outer membrane vesicles of Porphyromonas gingivalis: recent advances in pathogenicity and associated mechanisms - Wu, Zixiang; Long, Wei; Yin, Yi; Tan, Biyun; Liu, Chenyu; Li, Hongqiao; Ge, Song (Frontiers in Microbiology, 2025)
Periodontitis is a chronic infectious inflammatory disease primarily caused by periodontal pathogenic bacteria, which poses a significant threat to human health. The pathogenic mechanisms associated with Porphyromonas gingivalis (P. gingivalis), a principal causative agent of periodontitis, are particularly complex and warrant thorough investigation. The extensive array of virulence factors released by this bacterium during its growth and pathogenesis not only inflicts localized damage to periodontal tissues but is also intricately linked to the development of systemic diseases through various mechanisms. The outer membrane vesicles (OMVs) produced by P. gingivalis play a key role in this process. These OMVs serve as important mediators of communication between bacteria and host cells and other bacteria, carrying and delivering virulence factors to host cells and distant tissues, thereby damaging host cells and exacerbating inflammatory responses. The ability of these OMVs to disseminate and deliver bacterial virulence factors allows P. gingivalis to play a pathogenic role far beyond the confines of the periodontal tissue and has been closely associated with the development of a variety of systemic diseases such as cardiovascular disease, Alzheimer’s disease, rheumatoid arthritis, diabetes mellitus, non-alcoholic hepatitis, and cancer. In view of this, it is of great pathophysiological and clinical significance to deeply investigate its pathogenic role and related mechanisms. This will not only help to better understand the pathogenesis of periodontitis and its related systemic diseases but also provide new ideas and more effective and precise strategies for the early diagnosis, prevention, and treatment of these diseases. However, the current research in this field is still insufficient and in-depth, and many key issues and mechanisms need to be further elucidated. This article summarizes the recent research progress on the role of P. gingivalis OMVs (P. g-OMVs) in related diseases, with the aim of providing a theoretical basis and direction for future research and revealing the pathogenic mechanism of P. g-OMVs more comprehensively.